Perencanaan Jaringan Long Term Evolution (LTE) Berdasarkan Node B 3G Existing Di Kota Pekanbaru - Rahman, Fadrol; Febrizal, Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The Paper proposes Long Term Evolution (LTE) network design using of which is Node B data existing in the city of Pekanbaru. The design was involved several stages, those were collectingNode B data existing, the network planning based on the capacity, the network planning base on the coverage and the last did a final simulation planning using Atoll Software to get the configurationdesign based on coverage in the value calculation of link budget and cell radius required capital propagation channels. In this planning propagation models used Okumura-Hatta because thefrequency used is 700 MHz. Based on the obtained capacity planning cell maximum capacity is 150,84 Mbps, with the number of LTE subcribers as much as 1,979,972 users. The number ofeNode B needs to give on optimal service through the Pekanbaru city as many as 101 eNode B, with each cell radius to 10 km2 of Urban area, 13 km2 to Suburban area and 19 km2 to Rural area.Keywords : Planning by Capacity, Planning by Coverage, Okumura-Hatta, Software Atoll